Ultrastructural features of the hypopharyngeal glands in the social wasp Polistes versicolor (Hymenoptera : Vespidae) - Britto, Fabio Barros [UNESP]; Caetano, Flávio Henrique [UNESP] (Wiley-Blackwell, 2008)
The wasps of the genus Polistes have been considered the key to understanding the evolution of social behavior in Hymenoptera. Several studies have shown that the development of organized insect societies was accompanied by the evolution of structures like exocrine glands, which became specialized to perform specific functions. This article investigates the ultrastructural and cytochemical features of the hypopharyngeal glands of Polistes versicolor. These glands have been studied in depth in social bees, where they occur only in nurses and produce the royal jelly. Our results revealed that these glands basically did not vary among individuals or between sexes. They are constituted by spherical cells, each with a large nucleus and well-developed rough endoplasmic reticulum. Secretion vesicles are abundant, but lipid droplets were not observed, indicating that these glands may not have a role in pheromone synthesis. Acid phosphatase was detected in lysosomes, and also free in the cytosol, but did not seem to be related with cell death. Thus, our results suggest that the hypopharyngeal glands of P. versicolor may not have a specialized social role, but could produce digestive enzymes.
Keywords: cellular cycle; cytochemistry; hypopharyngeal glands; morphology; Polistes; wasps